Position-specific performance indicators that discriminate between successful and unsuccessful teams in elite women's indoor field hockey: implications for coaching. Issue 4 (16th February 2016) - Vinson, Don; Peters, Derek M.
Abstract: The aim of this investigation was to establish median performance profiles for the six playing positions in elite women's indoor hockey and then identify whether these position-specific profiles could discriminate between qualifying (top four), mid-table and relegated teams in the 2011–2012 England Hockey premier league. Successful passing in relegated teams was significantly lower ( P < 0.008) than in mid-table and qualifying teams in four of the five outfield positions. Furthermore, the right backs of qualifying teams demonstrated significantly fewer ( P < 0.008) unsuccessful passes (x̃ = 15.5 ± CLs 15.0 and 10.0, respectively) and interceptions (x̃ = 4.0 ± CLs 4.0 and 3.0, respectively) than relegated teams (x̃ = 19.5 ± CLs 21.0 and 17.0; x̃ = 7.5 ± CLs 8.0 and 6.0, respectively). Finally, the right forwards of relegated teams demonstrated significantly fewer ( P < 0.008) successful interceptions (x̃ = 4.0 ± CLs 5.0 and 4.0, respectively) than qualifying teams (x̃ = 5.0 ± CLs 6.0 and 3.0, respectively) and significantly more ( P < 0.008) unsuccessful interceptions (x̃ = 5.5 ± CLs 6.0 and 4.0, respectively) than mid-table teams (x̃ = 3.0 ± CLs 3.0 and 2.0, respectively). Based on these findings, coaches should adapt tactical strategies and personnel deployment accordingly to enhance the likelihood of preparing a qualifying team. Research should build from these data to examine dribbling, pressing and patterns of play when outletting.